الاتصال المسؤول للمنظمات: مبررات التوجه والمخاطر على السمعة - عتيق, معتز; نواري, امال (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
تعيش المنظمات اليوم في عالم تتزايد فيه التوقعات المجتمعية والبيئة تجاهها، والتي تميل نحو الممارسات الأخلاقية والمسؤولة، ليصبح رضا و ثقة كل الأطراف ذات المصلحة في المنظمة قضية رئيسية تتطلب منطق المسؤولية في أفعالها واتصالها. مما استوجب عليها اعتماد سياسات اجتماعية و بيئية ذات طبيعة تواصلية. و يعد الاتصال المسؤول أداة إستراتيجية تهدف إلى مواجهة تحديات المصداقية، الشرعية، الشفافية والمساءلة، كونه اتصال يترجم الالتزام الكلي للمنظمة إلى طرق ملموسة. إذ يأخذ في الاعتبار الجوانب البيئية والاجتماعية و المجتمعية للرسائل التي ينشرها، ولطرق الإرسال التي يستخدمها. ويروم هذا المقال أولا إلى استكشاف مبررات توجه المنظمات للاتصال المسؤول ، وثانيا إلى تسليط الضوء على مخاطر ه على سمعتها. Today, organizations live in a world in which there are increasing societal expectations and environment towards them, which prefer more ethical and responsible practices, so that the satisfaction of all interested parties and their confidence in the organization becomes a major issue that requires the logic of responsibility in their actions and communication. Consequently, organizations are obliged to adopt social and environmental policies of a communication. The Responsible communication is a strategic tool aimed at addressing the challenges of credibility, legitimacy, transparency and accountability. As, it is a communication translates the organization's total commitment into concrete ways. So, it takes into account the environmental, social and societal aspects of the published messages, and the transmission methods that it uses .This article aims firstly to explore the reasons for the organizations' orientation to responsible communication, and secondly to highlight the risks to their reputation.